PENGARUH MODEL PEMBELAJARAN SNOWBALL THROWING TERHADAP HASIL BELAJAR SISWA - Mukti Ratnasari; Marchasan Lexbin (IKIP Siliwangi, 2019)
This study aims to examine student learning outcomes using the type of snowball throwing learning towards student learning outcomes in mathematics subjects at MTs Islam Al-Maziyyah cianjur. The use of the method in this study is quasi-experimental with pretest and posttest equivalent to the control group design. Students of class VII Islamic MTs Al-Maziyyah cianjur which amounted to 3 classes were used as the population for this study while the research sample was class VII A as an experimental class that was treated with snowball throwing learning and VII C as a control class received normal learning treatment. The research instrument was in the form of student training experiments. The results showed that the influence of the relevant use of the type of snowball throwing learning was influenced on student learning outcomes from those using the usual approach.